A Two-step Technique for Neo-umbilicoplasty in the Abdominal Reconstructive Population. Issue 7 (July 2019) - Ngaage, Ledibabari M.; Kokosis, George; Kachniarz, Bartlomiej; Pedreira, Rachel; Rada, Erin M.; Nam, Arthur J.; Pearl, Jonathan; Kavic, Stephen; Rasko, Yvonne M.
Abstract : Summary: The umbilicus is the centerpiece of the abdomen and an important cosmetic landmark. Secondary intention healing can be used to create the illusion of an umbilicus in reconstructive surgery. However, there is a sparsity of literature on the role of neo-umbilicoplasty in this subset of patients and how they perceive their new umbilicus. We conducted a retrospective review of patients who received a neo-umbilicus during an abdominal reconstructive operation in 2016–2018. The umbilicus was amputated intraoperatively and tacking sutures were placed to create an indentation in the soft tissue; an inverted-V incision was sutured to create the illusion of an umbilicus. Postoperatively, patients were asked to rate their satisfaction with umbilicus appearance on a 5-point Likert scale. Of the 10 patients included; the majority were female (9:1), with a mean age of 37 years (range: 26–50) and mean BMI 29 (range: 21–38). The most common procedure performed at time of neo-umbilicoplasty was hernia repair (80%). There were no wound complications associated with the neo-umbilicus. Satisfaction was high (median 5, range: 1–5) and independent of time since surgery. Three patients gave scores below 5 and cited reasons of "lack of indentation" (n = 3, scores 4, 4, and 1), and "insufficiently notable scar" (n = 1, score 1). We hereby describe a simple surgical technique for neo-umbilicoplasty in patients undergoing reconstructive abdominal surgery that leads to long-lasting cosmetic satisfaction. Further studies of patient-reported outcomes and refinement of the technique will maximize the aesthetically pleasing results. Abstract : Supplemental Digital Content is available in the text.